Sam the Man & the dragon van plan - Dowell, Frances O'Roark (Sam the Man, 2018)
"When the family minivan needs replacing, Sam has the perfect plan to turn the new car into a monster minivan, complete with a dragon painted on it. But first, Sam has to convince his family why a monster minivan is the best choice--not to mention learn how to paint a dragon!"--